A Supraclavicular ALK-Positive Anaplastic Large-Cell Lymphoma Initially Misdiagnosed and Yet Successfully Treated with Wide Excision and Adjuvant Chemotherapy: a Case Report - Lekuya, Hervé Monka; Wamala Kalanzi, Edris; Mbiine, Ronald; Omoding, Abraham; Rosenwald, Andreas; Lemperle, Gottfried; Bringmann, Gerhard (SN Comprehensive Clinical Medicine, 2019)
ALK-positive Anaplastic Large-Cell Lymphomas (ALCL) are chemo-sensitive cancers; combination of histologic and immunophenotypic or genetic studies remains the main strategy to prevent their unnecessary surgical excision as they canmimic softtissues sarcomas in histology. In sub-Saharan Africa, however, availability and affordability of immunophenotypic studies, especially extended immunohistochemistry (IHC) tests, constitute major limitations for accurate diagnoses. The case presented herein is an example of a heavy surgical management resulting from an initially inaccurate diagnosis, but eventually treated successfully. Case presentation A 15-year-old female patient presented with a 5-month history of a painless right supraclavicular mass. The initial biopsies had conflicting histology reports. In view of its rapid growth, it was first managed surgically, as a high-grade sarcoma stage T4N1M0: a wide “en bloc resection” with primary flap covering was done. Post-operative histology with an extended IHC from the widely resected tissue finally revealed an ALK-positive ALCL, which proved to be sensitive to chemotherapy. An adjuvant chemotherapy of six cycles of CHOP regimen followed with a good response; the patient became clinically stable, and all the investigations that were done, including a PET-CT scan, could not detect any residual active disease. She was still disease-free at 2 years after completion of chemotherapy. Conclusions Although cost-effective, combined histologic and immunophenotypic studies, especially extended IHC tests, can reduce the incidence of misdiagnosed large-cell lymphoma. As exemplified in this present case, obtaining appropriate and sufficient tissue from the tumor could possibly increase the chance of finding an accurate diagnosis.
Keywords: Anaplastic large-cell lymphoma; Case report; Chemotherapy; Fascio-cutaneous flap; IHC; PET-CT scan; Misdiagnosis